Microplastic Presence in Antarctic Seawater and Surface Sediment Samples: Findings from the Turkish National Antarctic Scientific Expedition TAE-7 - Kara, Narin; Erkan, Hanife Sari; Celen, Meltem; Engin, Guleda Onkal (Central Fisheries Research Inst, 2025)
Increasing production and widespread use of plastics have led to an alarming increase in plastic waste, affecting remote regions such as Antarctica. Despite its isolation by currents, Antarctica experiences anthropogenic pollution transported by oceanic and atmospheric currents. This study focused on microplastic contamination in Lystad Bay, Antarctica. During the TAE-7 Antarctic Expedition, samples were collected from seawater, subsurface water and sediment sites at Lystad Bay. In seawater samples, an average microplastic concentration of 0.1055 +/- 0.0285 particles/m(2) (2.1102 +/- 0.5707 particles/m(3)) was found, predominantly fibres, and the dominant size ranges were found to be 500-999 (36.02% of all particles) mu m and 1000-1499 (22.01% of all particles) mu m. Polyethylene, polyamide and polyisoprene were the most commonly identified polymers. The mean particle concentration in the subsurface water samples was 11.2 +/- 5.5 particles/L, with fibers and fragments being the most common shapes. In the sediment samples, the average microplastic concentration was 0.895 particles/g DW, with fibers as the dominant shape. Six polymer types were identified, with polycarbonate and polyoxymethylene being the most common. The results highlight the pervasive impact of human activities and natural transport mechanisms on microplastic pollution in one of the most remote environments on Earth.
Keywords: Microplastics; Horseshoe Island; Lystad Bay; Sea surface water; Surface sediment